Estudio de un sistema de ubicación y localización a travéz de una red umts. - Juma Vacacela, Verónica Alexandra (2011)
This thesis presents the study and simulation of a Location System through a UMTS network, using different positioning methods such as: positioning based on cell coverage, positioning based on round trip time (RTT Round Trip time), positioning time of arrival (TOA) positioning angle of arrival (AOA), time difference of arrival (TDOA) and hyperbolic curves, and GPS-assisted method.